Pengaruh Gaya Kepemimpinan dan Etos Kerja terhadap Kinerja Karyawan : (Studi Kasus Perusahaan Manufakturing) - Sylvia Sisca Harlena; Istianah Setyaningsih (Jurnal Mahasiswa Manajemen dan Akuntansi, 2025)
This study aims to determine the effect of Leadership Style and Work Ethic on Employee Performance at PT. Samjin Indonesia. The research method used is a quantitative approach. Data collection was carried out using primary data obtained through questionnaires distributed to employees. The population in this study amounted to 955 people, and the sampling technique used the Slovin formula with a 5% margin of error, resulting in a sample of 282 respondents. The analytical method employed was multiple linear regression analysis with normality test, multicollinearity test, and heteroscedasticity test. Hypothesis testing was conducted using the t-test, F-test, and coefficient of determination analysis. Based on the results of the partial test, Leadership Style (X1) and Work Ethic (X2) partially show a positive and significant effect on Employee Performance (Y) at PT. Samjin Indonesia, with t-count values of 2.400 and 12.382, respectively, greater than the t-table value of 1.969. Meanwhile, the simultaneous test results show an F-count value of 125.442, greater than the F-table value of 3.03, indicating that Leadership Style (X1) and Work Ethic (X2) simultaneously have a significant effect on Employee Performance (Y). The coefficient of determination (R²) value of 0.473 indicates an influence of 47.3%, while the remaining 52.7% is influenced by other variables not examined in this study.